Phytochemical and Toxicity Analysis of Leucas zeylanica crude extracts - Abdullah, Faizuan; FaziraMohd Salleh, Noor Aida; Luqman Selahuddeen, Muhammad (Environmental and Toxicology Management, 2021)
Leucas zeylanica (L.) R. Br. (L. zeylanica) originated from Lamiaceae family which is also known as “Pokok ketumbit” by local Malaysian is famous for therapeutic treatment uses especially in India and Sri Lanka. Throughout this study, four different solvents which were n-hexane, chloroform, methanol, and distilled water used in the extraction method using cold maceration technique. Optimization was done and methanol became the best solvent that produced highest percentage yield compared to the other solvents and also been chose to carry out a few other analysis. The extracts were subjected to qualitative and quantitative analyses to determine the phytochemical constituents present in aerial parts of L. zeylanica. The Fourier Transform Infrared spectroscopy – Attenuated Total Reflection (FTIR-ATR) results showed few significance peaks according to extracted solvents. Qualitative analysis on the methanolic extract showed that L. zeylanica contains phenol, flavonoid and tannin through phytochemical screening tests using colorimetric method. The Gas Chromatography – Mass Spectrometry (GC-MS) results demonstrated few fatty acids been extracted in both n-hexane and chloroform extracts with high peak area, while Liquid Chromatography Tandem with Mass Spectrometry (LC-MS-MS) results identified that chloroform extract showed fragment spectrum of tricin [M+H]+ ion at m/z 328.1 with retention time of 19.49 min, while methanol extract had two fragment spectrum of tricin and apigenin at m/z 282.3 and 270.4 in positive ion mode at 19.53 min and 16.70 min respectively. Quantitative analysis on methanolic extract was done via Ultra Violet-visible spectrophotometric assay for estimation of total phenolic content (TPC), total flavonoid content (TFC) and total tannin content (TTC). TPC showed a gallic acid standard calibration curve, y = 0.0063x + 0.02 and estimated amount was 151.54 ± 0.04 mg of gallic acid equivalent/ 1 g of extract, meanwhile TFC displayed a quercetin standard calibration curve of y = 0.0050x + 0.037 and estimated amount of flavonoids was 71.76 ± 0.2 mg of quercetin equivalent/ 1 g of extract. Additionally, The toxicity test for the L. zeylanica extract showing that this compound is safe and non-toxic in term of skin irritation, cytotoxicity and also genotoxicity.